1993
DOI: 10.1128/jvi.67.6.3615-3619.1993
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of the leucine zipper-like motif of the human immunodeficiency virus type 1 envelope transmembrane glycoprotein

Abstract: The N-terminal region of the envelope (env) transmembrane protein of human immunodeficiency virus type 1 (HIV-1) has a leucine zipper-like motif. This highly conserved zipper motif, which consists of a heptad repeat of leucine or isoleucine residues, has been suggested to play a role in HIV-1 env glycoprotein oligomerization. This hypothesis was tested by replacing the highly conserved leucine or isoleucine residues in the zipper motif with a strong a-helix breaker, proline. We report here that such substituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(77 citation statements)
references
References 36 publications
3
74
0
Order By: Relevance
“…However, these same mutations eliminate membrane fusion activity by gp41 (5), a finding that suggests that the HRA mutations may compromise other conformations of the protein. The importance of HRA residues in the membrane fusion activities of HIV gp160 (5,8,15,59), Ebola virus GP (58), and severe acute respiratory syndrome coronavirus S (38) may perhaps suggest that the HRA regions of class I viral fusion proteins may, in general, undergo significant conformational changes during protein refolding. How-ever, determinations of the prefusion structures of these proteins are needed to confirm this hypothesis and reveal whether their HRA regions also adopt spring-loaded conformations analogous to those found in the prefusion structures of paramyxovirus F and influenza virus HA.…”
Section: Discussionmentioning
confidence: 99%
“…However, these same mutations eliminate membrane fusion activity by gp41 (5), a finding that suggests that the HRA mutations may compromise other conformations of the protein. The importance of HRA residues in the membrane fusion activities of HIV gp160 (5,8,15,59), Ebola virus GP (58), and severe acute respiratory syndrome coronavirus S (38) may perhaps suggest that the HRA regions of class I viral fusion proteins may, in general, undergo significant conformational changes during protein refolding. How-ever, determinations of the prefusion structures of these proteins are needed to confirm this hypothesis and reveal whether their HRA regions also adopt spring-loaded conformations analogous to those found in the prefusion structures of paramyxovirus F and influenza virus HA.…”
Section: Discussionmentioning
confidence: 99%
“…79, 2005 FUSION ACTIVITY OF EBV gH MUTANTS 12409 protein of Newcastle disease virus) and since this region was conserved in all three gammaherpesviruses analyzed, we decided to examine the importance of this region in EBV gH fusion with epithelial and B cells (11,26). Studies of HIV and other enveloped viruses have shown that hydrophobic residues, especially leucines, located in the coiled coils are important for the proper function of these regions in fusion (5,7,22,36). The putative coiled-coil domain of EBV gH contains four leucines; three of these are also conserved in rhesus and marmoset gH proteins.…”
Section: Location Of a Putative Coiled-coil Domain In Ebv Gh And Consmentioning
confidence: 99%
“…This self association may reflect their potential role in stabilizing the fusion attack complex as opposed to their involvement in oligomerization of the "native" envelope. A major support for this argument is that helix-disrupting mutations in the zipper domain fail to influence envelope oligomerization even though they render the envelope fusion incompetent (Dubay et al 1992, Chen et al 1993. indeed, borrowing again from the work of Carr and Kim (Carr & ICim 1993), it would appear that such domains may be unable to interact in the native oligomeric structure of the glycoproteins but, when subjected to certain triggering or activation events (pH drop in the case of the influenza HA), a dramatic conformational change occurs whereby these regions can associate and form coiledcoils.…”
Section: The Leucine Zipper Motif Of Gp41mentioning
confidence: 99%
“…The importance of the two helix motifs of gp41 not only is indicated by the potent anti-HIV activity of peptides and recombinant proteins discussed above but also by the functional assessment of the gp4l mutants (Dubay et al 1992, Chen et al 1993, Cao et al 1993. Of particular interest are the curious results that many non-conservative mutations in the C-terminal helix motif enhance the fusion ability of gp41 (Cao et al 1993) whereas mutations in the leucine zipper region tend to decrease or abolish the fusion activity of gp41 (Dubay et al 1992, Chen et al 1993. A possible explanation for this, consistent with the model presented Fig.…”
Section: Models For Hiv-1-mediated Fusionmentioning
confidence: 99%